Identification of SF-1 and FOXL2 and Their Effect on Activating P450 Aromatase Transcription via Specific Binding to the Promoter Motifs in Sex Reversing Cheilinus undulatus - Ji, Xinxin; Bu, Shaoyang; Zhu, Yi; Wang, Yi; Wen, Xin; Song, Feibiao; Luo, Jian (Frontiers in Endocrinology, 2022)
The giant wrasse Cheilinus undulatus is a protogynous socially hermaphroditic fish. However, the physiological basis of its sex reversal remains largely unknown. cyp19 is a key gender-related gene encoding P450 aromatase, which converts androgens into estrogens. cyp19 transcription regulation is currently unknown in socially sexually reversible fish. We identified NR5A1, encoding SF-1, and FOXL2 from giant wrasse cDNA and cyp19a1a and cyp19a1b promoter regions cloned from genomic DNA to determine the function of both genes in cyp19a1 regulation. Structural analysis showed that SF-1 contained a conserved DNA-binding domain (DBD) and a C-terminal ligand-binding domain (LBD). FOXL2 was comprised of an evolutionarily conserved Forkhead domain. In vitro transfection assays showed that SF-1 could upregulate cyp19a1 promoter activities, but FOXL2 could only enhance cyp19a1b promoter transcriptional activity in the HEK293T cell line. Furthermore, HEK293T and COS-7 cell lines showed that co-transfecting the two transcription factors significantly increased cyp19a1 promoter activity. The -120 bp to -112 bp (5’-CAAGGGCAC-3’) and -890 bp to -872 bp (5’-AGAGGAGAACAAGGGGAG-3’) regions of the cyp19a1a promoter were the core regulatory elements for SF-1 and FOXL2, respectively, to regulate cyp19a1b promoter transcriptional activity. Collectively, these results suggest that both FOXL2 and SF-1 are involved in giant wrasse sex reversal.